Analysis on Nonlinear Bending Behaviors of CFRP Beams by Section Partition Method. (2017) - Nasu, Momoka; Matsumoto, Takashi
Abstract: Carbon Fiber Reinforced Polymer, CFRP, is a promising material for application to bridge girders. However, as CFRP beams show nonlinear behaviors, be it in normal and shear strain directions, it is necessary to develop a method to obtain the deflection of CFRP beams by considering both the bending and shear deflection component. This study aims to verify the effectiveness of section partition method to reproduce the behaviors of CFRP beams that have been tested in an earlier experiment. The beams studied are box beams, composed of carbon fiber and epoxy resin.